NILAI KETUHANAN DAN AKHLAK DALAM EKONOMI ISLAM DALAM PERSPEKTIK AL-QURAN SEBAGAI SOLUSI DARI KELEMAHAN SISTEM EKONOMI KAPITALIS - Hermansyah (STAI Dirosat Islamiyah Al-Hikmah Jakarta, 2024)
Islamic economics has its own uniqueness and privileges compared to all economic systems that exist in the world today, such as the capitalist economy and the socialist economic system. Among these special values ??include divine and human values ??as well as morals. With these three values, Islamic economics overcomes all problems that exist in society and provides solutions for the welfare of human life and their prosperity in this world and the hereafter. Meanwhile, capitalist economics teaches its adherents to obtain as much profit as possible without caring about how to achieve it and also does not pay attention to human values ??and morals, resulting in socio-economic inequality in society due to practicing capitalist economic theory. This article tries to discuss these three values ??so that they can be understood by readers and the general public.